UV-Cured polypropylene mesh-reinforced composite polymer electrolyte membranes - ÇAKMAKÇI, EMRAH (WALTER DE GRUYTER GMBH, 2015)
In this study, a polypropylene (PP) mesh was used to prepare proton- and Li+ conducting composite membranes for fuel cells and lithium rechargeable batteries, respectively. For the preparation of Li+ conducting membrane, polypropylene mesh was first immersed in an electrolyte solution, which was composed of LiBF4 and ethylene carbonate. Then the swollen membrane was immersed in an acetone solution of polyethylene glycol diacrylate (PEGDA), polyvinylidenefluoride-co-hexafluoro-propylene and photoinitiator. Finally, PP fabric was taken out from the solution and exposed to UV irradiation. Furthermore, proton conducting membranes were prepared by immersing the PP mesh into a mixture of vinyl phosphonic acid, PEGDA and photoinitiator. Afterwards, samples were cured under UV light. PP-reinforced membranes designed for fuel cell applications exhibited a room temperature conductivity of 3.3x10(-3) mS/cm, while UV-cured electrolyte for Li batteries showed ionic conductivities in the range of 1.61x10(-3)-5.4x10(-3) S/cm with respect to temperature. In addition, for lithium-doped composite polymer electrolyte (CPE), the electrochemical stability window was negligible below 4.75 V vs. Li/Li+. It is concluded that lithium-doped CPE has suitable electrochemical stability to allow the use of high-voltage electrode couples.
Keywords: composite polymer electrolyte; fuel cells; ionic conductivity; lithium batteries; UV curing; GEL ELECTROLYTE; LITHIUM